Encyclopedic dictionary “Modern History (World and Romanian)”; by Lidia Prisac, Ion Valer Xenofontov; Chișinău, 2023 - Ivan Duminica (Енциклопедичний Вісник України)
This review examines the encyclopedic dictionary “Modern History (global and Romanian)”, published in Chisinau in 2023. The reference book contains over 2300 encyclopedia entries dedicated to significant events, phenomena, processes, and prominent figures of the 20th and 21st centuries. The reviewed work rightfully pays significant attention to the history of Bessarabia, the Moldavian ASSR, the Moldavian SSR, and the Republic of Moldova. However, there is a considerable amount of information related to Ukraine. This review delves into the dictionary’s coverage of Ukraine, highlighting encyclopedia entries on the state, key figures, some globally known tragic events, and the country’s complex historical trajectory.